Occupational therapy and physical dysfunction : enabling occupation. - 4 0 16; Ed. D. Curtin, Michael,;Molineux, Matthew.;Supyk-Mellson, Jo-anne.; 5 (Edinburgh ;;New York : Churchill Livingstone/Elsevier, 2010)
The sixth edition of this classic book remains a key text for occupational therapists, supporting their practice in working with people with physical impairments, stimulating reflection on the knowledge, skills and attitudes which inform practice, and encouraging the development of occupation-focused practice. Within this book, the editors have addressed the call by leaders within the profession to ensure that an occupational perspective shapes the skills and strategies used within occupational therapy practice. Rather than focusing on discrete diagnostic categories the book presents a range of strategies that, with the use of professional reasoning, can be transferred across practice settings.--Publisher's description.
Defining occupational therapy / Clare Wilding -- The nature of occupation / Matthew Molineux -- Occupational therapy: a disability persepective / John Swain and Sally French -- Contesting assumptions in occupational therapy / Karen Whalley Hammell -- Occupational reasoning / Joan Rogers -- Understanding models of practice / Jo Supyk and Jacqui McKenna -- Process of assessment and evaluation / Clare Hocking -- Writing occupation focussed goals / Julia Bowman and Lise Mogensen -- Enabling skills and strategies / Michael Curtin -- The art of person-centred practice / Thelma Sumsion -- Occupation in context / Gail Whiteford -- Enabling communication in a person-centred, occupation-focussed context / Sue Baptiste -- Analysis of occupational performance / Gill Chard -- Psychosocial support / Jacqui McKenna -- Advocating and lobbying / Valmae Rose, Kevin Cocks and Lesley Chenowich -- Educational strategies / Tammy Hoffman -- Health promotion and occupational therapy / Rachael Dixey -- Working with groups / Claire Craig and Linda Finlay -- Community development / Nick Pollard, Dikaios Sakellariou and Frank Kronenberg -- Developing partnerships to privilege participation / Roshan Galvann, Peliwe Mdlokolo and Robin Joubert -- Working towards inclusive communities / Hanneke van Bruggen -- Community based rehabilitation: opportunities for occupational therapists in an evolving strategy / Kirsty Thompson, Christina Parasyn and Beth Fuller -- Entrepreneurial opportunities in the global community / Marilyn Pattison -- Enabling engagement in self care occupations / Helen van Huet ... [et al.] -- Leisure / Ben Sellar and Mandy Stanley -- Play / Karen Stagnitti -- Work rehabilitation / Catherine Cook and Sue Lukersmith -- Home modification: occupation as the basis for an effective practice / Catherine Bridge -- Towards universal design / Leslie C. Young, Andrew P. Payne and Sharon Joines -- Assistive devices for enabling occupations / Helen Pain and Sue Pengelly -- Wheelchairs: posture and mobility / Rachael MacDonald -- Driver assessment and rehabilitation within the context of community mobility / Marilyn Di Stefano and Wendy Macdonald -- Orthotics for occupational outcomes / Natasha Lannin and Iona Novak -- Biomechanical strategies / Janet Golledge -- Skills for addressing sensory impairments / Farieda Adams and Michelle Morcom -- Moving and handling strategies / Maggie Bracher and April Brooks -- Optimising motor performance following brain impairment / Annie McCluskey, Natasha Lannin and Karl Schurr -- Cognitive and perceptual strategies / Carolyn A. Unsworth -- Strategies for sensory processing disorders / Deborah Windley.
Rev. ed. of: Occupational therapy and physical dysfunction / edited by Annie Turner, Marg Foster, Sybil E. Johnson. 5th ed., 2002.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; rehabilitation. -- Occupational therapy.;Occupational Therapy.;Disabled Persons -- 20; 20; 2